Аналіз діяльності закладів ресторанного господарства Північно-Західного економічного району України - Єрко, Ірина; Yerko, Irina (My University, 2016)
Досліджено заклади ресторанного господарства Північно-Західного економічного району України. Установлено, які типи підприємств відносять до закладів ресторанного господарства. Проаналізовано наукові дослідження із цієї тематики. Охарактеризовано кількісні та якісні показники діяльності закладів ресторанного господарства. Досліджено територіальне розміщення закладів ресторанного господарства району. Установлено, що більшість підприємств ресторанного господарства Північно-Західного економічного району України складають ресторани, бари, кафе із середньою кількістю працівників від п’яти до 20 осіб. Проаналізовано обсяг роздрібного товарообороту підприємств. Установлено, що для вдалого соціально-економічного розвитку регіону потрібно розрахувати показник забезпеченості міського та сільського населення мережею ресторанного господарства. Подано характеристику закладів ресторанного господарства за типами, а саме: ресторани, кафе, бари, їдальні й постачання готової їжі. Визначено основні проблеми розвитку закладів ресторанного господарства економічного району. Institutions of restaurant business of North-Western economic region of Ukraine have been explored. It has been established which types of enterprises belong to institutions of restaurant business. Scientific researches from this theme have been analyzed. Territorial placement of institutions of restaurant business in the region have been explored. It is established, that the majority of institutions of restaurant business of North-Western economic region of Ukraine consists of restaurants, bars, cafes with the average number of workers from 5 to 20 workers. Quantity of retail commodity turnover have been analyzed. It has been set, that you have to calculate the provision indicator of urban and village citizens with restaurant chains to have successful social and economic development of the region. Characteristics of institutions of restaurant business by types, speaking about restaurants, bars, cafes, dining-rooms and providing with prepared food is given. Major development problems of institutions of restaurant business in the economical region have been identified.
Analysis of the Institutions of Restaurant Business in North-Western Economic Region of Ukraine
Keywords: ресторанне господарство; заклади ресторанного господарства; ресторан; бар; кафе; їдальня; Північно-Західний економічний район; restaurant business; institutions of restaurant business; restaurant; bar; cafe; dining-room; NorthWestern economic region